In-Company Technical Training in Developing Countries - Murray, Stephen; Aguado, Cesar; Castaño, Victor M. (Journal of Education and Training, 2022)
The article speaks about the need for training within the company; the company’s role in the provision of training; the measurement of training (its success, etc.); what its role is in training provision; and what might be the evolution of its training commitment after its provision has been established.